Characterization of Poultry Production Systems in Vietnam - Burgos, S.; Hanh, P. T. Hong; Roland-Holst, D.; Burgos, S.A. (International Journal of Poultry Science, 2007)
Poultry raising in Vietnam is widespread and common to smallholder farmers that keep chickens and ducks as a source of cheap animal protein and to derive income from the sale of eggs, meat and live birds. Three systems of poultry production are described: 1) traditional, extensive backyard/household poultry production, 2) semi-intensive, small to medium scale, market-oriented, commercial poultry production and 3) intensive, large scale, industrial poultry production.